Design and rationale of ProSar, the first Danish sarcoidosis registry - Møller, Janne; Hilberg, Ole; Bendstrup, Elisabeth (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2022)
Background: The clinical presentation and disease course in sarcoidosis are highly heterogenic and varies among ethnic groups. Incidence and prevalence of sarcoidosis in Scandinavian countries are high. Though sarcoidosis is generally a benign disease, the overall risk of death in individuals with sarcoidosis is higher compared with the general population. Information on epidemiology, health status, treatment, distinct phenotypes, genotypes and course of sarcoidosis is limited. Systematic data registration is important to characterize patients with sarcoidosis and to enhance the understanding of the disease. To address this, we developed the first Danish sarcoidosis registry, ProSar.Objective: To describe the design and rationale of the noninterventional, prospective, and observational Danish sarcoidosis registry.Methods: The registry was designed by respiratory physicians in collaboration with specialist representatives from the fields of extrapulmonary organ involvement. The registry includes individual data on patient demographics, family history, referral patterns, symptoms, pulmonary and extra-pulmonary organ involvement, comorbidities, treatment and diagnostic investigations as well as patient reported outcome measures relevant to sarcoidosis. Eligible patients are Danish adults diagnosed with sarcoidosis able to read and understand Danish.Conclusion: The first Danish sarcoidosis registry, ProSar, will collect prospective epidemiological data including clinical characteristics, referral patterns, disease trajectories and treatment pathways in Danish patients with sarcoidosis. The registry is expected to facilitate improved medical management and outcome for patients and future sarcoidosis research.